Kepemimpinan Kharismatik dalam Perspektif Pendidikan Islam - Gunawan, Ade; Pratama, Dandy Putra; Hasri, Salfen; Sohiron, Sohiron (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
Leaders are easily distinguishable because of their unique combination of skills, experiences, and temperament. Leadership styles have significant effects on the organizations they are used to guide, both positively and negatively. The purpose of this research is to provide a solution to the question of what charismatic leadership means from the viewpoint of Islamic education. Throughout this work, I have relied heavily on research conducted in libraries. Since a qualitative methodology was used, this study falls under the heading of